1994
DOI: 10.1111/j.1476-5381.1994.tb17148.x
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the mechanisms involved in the inflammatory response in a reversed passive Arthus reaction in guinea‐pig skin: contribution of neutrophils and endogenous mediators

Abstract: 1 Mediators of inflammation can increase vascular permeability in at least two different ways: by acting directly on endothelial cells or, indirectly, through an incompletely understood mechanism, dependent on circulating neutrophils. Neutrophil-dependent oedema formation has been described in the skin of rabbits, rats, hamsters, mice and man. In contrast, we presented evidence in a previous study that local oedema formation induced by i.d. injection of chemoattractants in guinea-pig skin was neutrophil-indepe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0

Year Published

1996
1996
2004
2004

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 27 publications
2
24
0
Order By: Relevance
“…Depletion studies have confirmed the requirements for immune complexes and complement for the full expression of injury [1,6,7]. In addition, neutrophil recruitment is believed to be important in the initiation and mediation of this reaction [7]. Early studies have concentrated on the contribution of complement in recruiting the effector cells of the reaction, neutrophils [1,6].…”
Section: Introductionmentioning
confidence: 99%
“…Depletion studies have confirmed the requirements for immune complexes and complement for the full expression of injury [1,6,7]. In addition, neutrophil recruitment is believed to be important in the initiation and mediation of this reaction [7]. Early studies have concentrated on the contribution of complement in recruiting the effector cells of the reaction, neutrophils [1,6].…”
Section: Introductionmentioning
confidence: 99%
“…21,22 However, our current study using the PMN-depleted animal clearly demonstrated that the ZAP-induced plasma protein extravasation in guinea-pig skin is composed of two different mechanisms, one PMN-dependent and the other PMN-independent. This result is consistent with the previous report using the rabbit skin.…”
Section: Discussionmentioning
confidence: 90%
“…21,22 So, we examined whether the ZAP-induced PMN-independent plasma extravasation could be suppressed with an antihistaminic agent, triprolidine. To evaluate the effect exclusively on the PMN-independent response, we measured the plasma extravasation for initial 30 min in the PMN-depleted guinea-pigs pretreated with cyclophosphamide.…”
Section: Pmn-dependency and -Independency Of Zap-induced Plasma Protementioning
confidence: 99%
“…1). Platelet–activating factor and neutrophils have been shown to play important roles in rat, guinea pig and rabbit Arthus reaction models [36, 37, 38]. Platelet–activating factor antagonists attenuated the cutaneous Arthus reaction including the late VPE in the three animal models [37].…”
Section: Discussionmentioning
confidence: 99%